Dietary antioxidants remodel DNA methylation patterns in chronic disease. (23rd December 2019) - Beetch, Megan; Harandi‐Zadeh, Sadaf; Shen, Kate; Lubecka, Katarzyna; Kitts, David D.; O'Hagan, Heather M.; Stefanska, Barbara
Abstract : Chronic diseases account for over 60% of all deaths worldwide according to the World Health Organization reports. Majority of cases are triggered by environmental exposures that lead to aberrant changes in the epigenome, specifically, the DNA methylation patterns. These changes result in altered expression of gene networks and activity of signalling pathways. Dietary antioxidants, including catechins, flavonoids, anthocyanins, stilbenes and carotenoids, demonstrate benefits in the prevention and/or support of therapy in chronic diseases. This review provides a comprehensive discussion of potential epigenetic mechanisms of antioxidant compounds in reversing altered patterns of DNA methylation in chronic disease. Antioxidants remodel the DNA methylation patterns through multiple mechanisms, including regulation of epigenetic enzymes and chromatin remodelling complexes. These effects can further contribute to antioxidant properties of the compounds. On the other hand, decrease in oxidative stress itself can impact DNA methylation delivering additional link between antioxidant mechanisms and epigenetic effects of the compounds. Linked Articles: This article is part of a themed section on The Pharmacology of Nutraceuticals. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.6/issuetoc